First Mapping Experiment of the Infrastructure & Facility Asset Management Knowledge Developement in JMAIF and Reflexion on Scientific Paper Stipulation for JMAIF - Hitapriya Suprayitno; Ria Asih Aryani Soemitro (Jurnal Manajemen Aset Infrastruktur & Fasilitas, 2018)
Infrastructure & Facility Asset Management knowledge need to be developed. JMAIF has been established, among others, to develop this knowledge. Knowledge Development Framework has been proposed. A mapping experiment need to be executed. The experiment shows, that among the 6 knowledge blocks, it is only 4 blocks which are filled. Three actions need to be executed : writting 5 Basic Knowledge in sequence, improving the Framework and executing Cross Mapping. Paper stipulation concerns scientific requirement and paper type needed. Sientific requirements are based on fact, logic, new, never been published. Types of scientific paper needed for JMAIf are : idea paper, characteristic paper, profesional experience paper, research paper, review paper.